(untitled) (Journal of Laboratory Animal Science, 2024)
GLP is a Quality system concerned with the organizational process and the conditions under which non-clinical health and environmental safety studies are planned, performed, monitored, recorded, reported and archived. The purpose of studies on “non-clinical health and environmental safety” is to investigate the physical/chemical, biological and/ or toxicological properties of the test item under investigation. The GLP principles are not only concerned about the possibility for checking back the identity of the test item but also ensures that the correct test item has been applied to the test systems. Test system characterization is an important quality control criterion in GLP studies. Regulators need sound, healthy, valid, unbiased test systems, to obtain reproducible, repeatable and reliable test results. This is possible only when we use properly characterized, pure, healthy test systems at a globally harmonized environmental conditions.